SOLUSI LEGALITAS DAN MANAJEMEN USAHA UNTUK UMKM DI DESA LABUHAN RATU 1 KECAMATAN WAY JEPARA KABUPATEN LAMPUNG TIMUR - Putri, Sastya; Faiqoh, Dina Nadiyah; Setiowati, Reni Diah; Yulianti, Tri Endang (Batara Wisnu : Indonesian Journal of Community Services, 2024)
This PKM activity is carried out in Labuhan Ratu Village, Way Jepara District, and is aimed at MSME entrepeneurs in Labuhan Ratu 1 Village, which consists of a variety of culinary businesses. PKM is conducted to provide business operators with an understanding of factors that support their business, such as legality and management, so that the business does not only focus on profit but can also develop in the future by paying attention to and applying these supporting factors. Therefore, PKM is conducted to provide an understanding of business legality. There are three stages in the method of implementing activities. First is the preparation. This includes pre-survey, team formation, proposal creation and submission, team and partner coordination, and preparation of training tools and materials. The second stage is program socialization. This is done through counseling 9presentation of material) and discussion. The third stage is evaluation are compared before and after the program implementation through interviews and observations. After that, a report is prepared for publication. The sozialization discusses brand, legality, and marketing strategies. After the socialization, there were several outcomes and external activities produced. First, business actors gained a better understanding of the function of trademarks and their legality, and they began implementing trademark registration to obtain legal protection for their trademarks. Second, entrepeneurs learn about brands as a marketing strategy and they make their brands attractive and sellable. The societal value system in the field of Education, especially in economics and law, is improved with this program.